Distracting and risky behaviours while cycling: a comparison of group and non-group riders in Western Australia. Issue 6 (19th August 2017) - Fraser, Michelle; Meuleners, Lynn B; Chow, Kyle; Stevenson, Mark R
Abstract : Background: Use of mobile phones and portable audio equipment and alcohol are known to negatively affect cycling ability. Evidence suggests that cyclists may be less likely to engage in these behaviours while riding in a group; however, it is unknown whether group riders are also at reduced risk when participating in non-group riding. Objective: To examine the association between group riding participation and the use of mobile phones and portable audio equipment and alcohol while non-group riding in Perth, Western Australia. Methods: A cross-sectional analysis of an online questionnaire was undertaken. Group and exclusive non-group riders were compared and separate binary logistic regression models were used to examine the association between group riding participation and the use of mobile phones and portable audio equipment and alcohol while non-group riding, controlling for gender, age, education and frequency of non-group riding. Results: Participants included 365 cyclists: 187 exclusive non-group riders (51.2%) and 178 group riders (48.8%). Group riders were less likely to have possibly cycled while over the legal blood alcohol limit in the past 12 months (OR: 0.56, 95% CI 0.34 to 0.92) and were less likely to ever use portable audio equipment (OR: 0.57, 95% CI 0.34 to 0.94) than exclusive non-group riders, while participating in non-group riding. Group riding status was not associated with mobile phone use. Conclusions: This study provides early evidence that there may be differences between group and non-group riders that impact on their safety behaviours while participating in non-group riding.